Green Marketing – an Eco Friendly Marketing New Opportunities and Challenges: Exploring the Potential of Green Marketing (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Today, in the scenario of global concern for environment issue, theterm green marketing is gaining importance among all the marketers in theworld. Green marketing refers to holistic marketing concept wherein theproduction, marketing consumption of an disposal product and service, happen ina manner that is less detrimental to the environment with growing the awarenessabout the implications of global warming, non-biodegradable soild waste,harmful impact of pollutants etc. Both Markets and consumes becomingincreasingly sensitive the need for swith in to the green product and services.Green marketing was given prominence in the late 1980s and 1990 after theproceeding the first workshop on ecological Marking held in Austin, texas in1975. This paper tries to explain the new opportunities and challenges of GreenMarketing.